New record of interactions between spotted skunk (Spilogale sp.) and gray fox (Urocyon cinereoargenteus) in Nayarit, México - Luja, Víctor H.; Zamudio, Maria G. (Therya Notes, 2024)
To understand the dynamics of terrestrial ecosystems, it is essential to study the interactions between different species. These interactions (predation, mutualism, competition and parasitism) play a crucial role in regulating populations and distribution of species. Camera traps were used to record the biodiversity of the La Montaña Encantada Natural Park, Municipality of Xalisco, Nayarit. Three records of interaction were obtained between a spotted skunk (Spilogale sp.) and the gray fox (Urocyon cinereoargenteus). In the videos obtained, the skunk follows the fox very closely; in one of them the fox even comes back to look for him. These reports of interaction between skunks and foxes (the first recorded in the oak forest in western México), are added to those obtained for the arid ecosystems of the Tehuacán-Cuicatlán Biosphere Reserve, Puebla and in the tropical forest of the Península of Yucatán. Interactions between gray fox and skunks also occur in oak forests of Nayarit. It is necessary to carry out specific studies to understand the causes and consequences of these interactions.